Structural and dynamical characterization of water on the Au (100) and graphene surfaces: A molecular dynamics simulation approach - Foroutan, Masumeh; Darvishi, Mehdi; Fatemi, S Mahmood (Physical review. E, 2017)
The positioning, adsorption, and movement of water on substrates is dependent upon the chemical nature and arrangement of the atoms of the surface. Therefore the behavior of water molecules on a substrate is a reflection of properties of the surface. Based on this premise, graphene and gold substrates were chosen to study this subject from a molecular perspective. In this work, the structural and dynamical behaviors of a water nanodroplet on Au (100) and the graphene interfaces have been studied by molecular dynamics simulation. The results have shown how the structural and dynamical behaviors of water molecules at the interface reflect the characteristics of these surfaces. The results have demonstrated that residence time and hydrogen bonds' lifetime at the water-Au (100) interface are bigger than at the water-graphene interface. Energy contour map analysis indicates a more uniform surface energy on graphene than on the gold surface. The obtained results illustrate that water clusters on gold and graphene form tetramer and hexamer structures, respectively. Furthermore, the water molecules are more ordered on the gold surface than on graphene. The study of hydrogen bonds showed that the order, stability, and the number of hydrogen bonds is higher on the gold surface. The positioning pattern of water molecules is also similar to the arrangement of gold atoms while no regularity was observed on graphene. The study of dynamical behavior of water molecules revealed that the movement of water on gold is much less than on graphene which is in agreement with the strong water-gold interaction in comparison to the water-graphene interaction.